Experiences and support needs of older care givers caring for family members (or friends) with cancer. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Bailey, Chris; Seymour, Kim Chivers; Duke, Sue; Moore, Mike
Abstract : Background: 77% of cancer deaths occur in people aged 65 years and over. However, research has largely focused on younger adults, leading to a lack of understanding of the complex needs of older adults with cancer and their family care givers. Aims: To explore the experience and support needs of older family care givers in end of life care. Methods: A longitudinal study using indepth interviews and structured measure of service use (OMFAQ). 25 pairs were recruited via specialist palliative care nurses, comprising one person with cancer and their lay care giver, all aged 65 years and over. Mean age was 78 years. Mean length of relationships was 44 years. 25 indepth interviews were conducted; 19 second interviews two to four weeks later and 11 final interviews 6 months after the first. Data analysis was based on the process of microanalysis, constant comparison and theory development described by Strauss and Corbin (1998, 2008). Results: A theoretical model of family caregiving was developed which suggests that the experience of family caregiving is characterised by a sense of anticipated loss in the context of which ties of duty and loyalty exert a strong influence. Arising from this central experience are a range of caregiving strategies, notably care management, maintaining the household and negotiating relationships with health and social care professionals, that focus on achieving a sense of equilibrium or containment across physical, functional and emotional domains. Conclusions: The pressure to keep up with the responsibilities of caregiving leads to a strict scheduling of day-to-day life. Maintaining a sense of good governance within this concentrated and condensed physical and metaphysical space can be difficult. Supportive interventions are needed for care givers and should focus on providing relief from the difficulty of accommodating caregiving demands, and the tendency towards an increasingly tightly boundaried day-to-day life.